An Extensive Replication Study on Three New Susceptibility Loci of Primary Angle Closure Glaucoma in Han Chinese: Jiangsu Eye Study - Haihong Shi; Rongrong Zhu; Nan Hu; Jian Shi; Junfang Zhang; Linjuan Jiang; Hong Jiang; Huaijin Guan (Journal of Ophthalmology)
Genome-wide association study (GWAS) analysis identified three new susceptibility loci for PACG. In this study, we aimed to investigate whether these three loci in PLEKHA7, COL11A1, and PCMTD1-ST18 are associated with PAC and ocular biometric characteristics, such as axial length (AL), anterior chamber depth (ACD), and diopter of spherical power (DS). The study was a part of the Jiangsu Eye Study. The samples were collected from 232 PAC subjects and 306 controls from a population-based prevalence survey conducted in Funing County of Jiangsu, China. The single nucleotide polymorphisms (SNPs) of rs11024102 in PLEKHA7, rs3753841 in COL11A1, and rs1015213 in PCMTD1-ST18 were genotyped by TaqMan-MGB probe using the RT-PCR system. None of the three polymorphisms showed differences in the distribution of genotypes and allele frequencies between the PAC group and the control group. No significant association was determined between the 3 SNPs and AL, ACD, or DS of PAC subjects. We concluded that even though PLEKHA7 rs11024102, COL11A1 rs3753841, and PCMTD1-ST18 rs1015213 are associated with PACG, those sequence variations are not associated with PAC in a Han Chinese population. Our results also did not support a significant role for these three SNPs in ocular biometry such as AL, ACD, and DS.